Detection of periapical lesion development by conventional radiography or computed tomography - Jorge, Erica G.; Tanomaru-Filho, Mario [UNESP]; Gonçalves, Marcelo [UNESP]; Tanomaru, Juliane Maria Guerreiro [UNESP] (Mosby-elsevier, 2008)
Objective. The aim of this study was to detect the development of experimentally induced periapical lesions using conventional radiography and computed tomography.Study design. The root canals of dogs' teeth were exposed to the oral environment for 7 days for contamination and then sealed for 7 days (GI), 15 days (GII), 30 days (GIII), and 60 days (GIV). Immediately after each experimental period, radiographs and tomograms were taken in order to detect the occurrence of periapical bone resorption. The periapical radiographs were digitized and areas of bone resorption were measured using the VIXWIN 2000 software. Scores were assigned to the tomograms based on the progression of periapical bone resorption. The specimens were evaluated by calibrated examiners who were blinded to the groups. The radiographic results were analyzed by ANOVA and Tukey's test (P <.05) and the tomographic results were analyzed by Kruskal-Wallis and Dunn's tests (P <.05).Results. The radiographic evaluation did not reveal periapical lesions at the 7-day control. Lesions were radiographically visible at 15 and 30 days (47.4% and 77.8% of the cases, respectively) and presented similar dimensions (P <.05). At 60 days, lesions were detected in all specimens, presenting larger dimensions than those of the earlier evaluation periods (P <.05). The tomographic evaluation detected lesions at 7 and 15 days (32.5% and 83.3% of the cases, respectively). Lesions were detected in all specimens at the 30- and 60-day periods, when the greatest values of bone resorption were observed (P <.05).Conclusions. Tomography was able to detect periapical lesion development in its initial stages, even when the lesions were undetectable radiographically.